A spatio-temporal framework for sustainable planning of buildings based on carbon emissions at the city scale. (July 2022) - Abu Dabous, Saleh; Shanableh, Abdallah; Al-Ruzouq, Rami; Hosny, Fatma; Khalil, Mohamad Ali
Highlights: An integrated spatio-temporal life cycle framework is developed. Assessed CO2 emission for building construction and operation. Analyzed the impact of using different materials and building construction systems. Identified CO2 hot spots at the urban level. Analyzed retrofitting scenarios and associated improvements. Abstract: Buildings are key society element and essential in the formation of sustainable cities. Several studies focused on life cycle assessment of construction materials while limited research analyzed CO2 emissions associated with buildings. This research proposes a spatio-temporal framework to analyze CO2 emissions of buildings applied at the city scale to assist in planning and decision-making of buildings construction and operation. The embedded methods within the framework can identify locations of high-intensity CO2 emissions in a city and recommend retrofitting actions to resolve these hotspots. The framework analysis is applied to the city of Ajman in the United Arab Emirates that had witnessed major expansion. The findings indicate that the embodied carbon emissions equivalents (ECEE) for buildings construction had increased from 7, 095 Kt to 9, 064 Kt, and then to 12, 680 Kt in the years 1986, 2005, and 2015, respectively, and the ECEE for buildings operation had increased from 1, 389 Kt/year to 1, 919 Kt/year, and then to 2, 547 Kt/year in the years 1986, 2005, and 2015, respectively. The recommended retrofitting actions for Ajman developed through the analysis can reduce total CO2 emissions of buildings operation by 14%. Future work can consider additional sustainability indicators within the proposed framework.